EFFECTIVENESS OF PLYOMETRICS AND POWER TRAINING METHODS ON VERTICAL JUMP PERFORMANCE IN CHILDREN'S VOLLEYBALL (Fiep Bulletin - online, 2011)
Becomes evident on literature that the devecopment of the explosive strengh for vertical jump is essential on volleyball players. Therefore, present studies main objective is to verify with method of explosive trengh training is more effective (plyometrics or power training) to optimize the development of the vertical jump, after 16 week of training on teenagers volleyball's athletes (14 to 17 years old). For this, 20 volleyball athletes from kids and youth category of both genders, mode two experimental groups (plyometric's group and power training's group) and execute a training of eight weeks with two weekly section. Vertical Jump (VJ) test were mode before and after training for data avaliation. The results obtain from both groups were compare through the T of Student's test paired and through the andire of varience (ANOVA). There have been on both groups non-significant improvement.
Keywords: explosive strength; plyometrics; power training; vertical jump; volleyball